Kemiskinan dan Strategi Pengentasannya (Studi Manajemen Strategik dalam Upaya Penanggulangan Kemiskinan di Kabupaten Kutai Kartanegara, Kalimantan Timur) - Mohammad Asrie Hamzah; M. Syafi’i Idrus; Djumilah Zain; Djumahir - (Jurnal Aplikasi Manajemen, 2012)
Poverty overcoming needs a strategic management because every planning and execution of related activities in a certain long term period have to be evaluated, which its result will be considered in making correction for further planning and program. Concept of empowerment is the most exact method reducing poverty and there should be full concentration of development in grassroots level. This approach focuses on the ability of improving either technical or managerial skills. Another relevant characteristic is development growth performed with a great attention on environmental resources, as well as human resources. Local potential is the basic asset to be a consideration priority of the development activities to be executed. The cause of poverty in Kutai Kartanegara Regency is the combination of structural, cultural, and natural factors altogether, added by factor of entering migration. In reducing poverty, there are some programs, such as: Financial Aid for the Poor, education subvention, healthcare subvention, County Fund Allocation, road hardening in every county, the construction of main road connecting 5 districts in Upstream Kutai, which is still on-going, and National Program of Society Empowerment using joined fund between Central and Local Government. There should be improvement in managing poverty alleviation in Kutai Kartanegara Regency, either in planning, in executing, in monitoring, or in evaluating so that the program may directly have effects on the poor.Keywords: poverty, strategic management, empowerment